Effect of hydrogen on semiconductive properties of passive film on ferrite and austenite phases in a duplex stainless steel - L. Q. Guo (Nature Portfolio, 2017)
Abstract Hydrogen effect on semiconductivity and compositions of passive films formed on ferrite and austenite phases in a duplex stainless steel were investigated by current sensing atomic force microscopy and X-ray photoelectron spectroscopy. It is demonstrated that hydrogen significantly increases the conductivity of passive film due to the increase of OH−/O2− ratio. The passive film on austenite has higher conductivity than that on ferrite after hydrogen charging due to more hydrogen in austenite. The presence of hydrogen causes an inversion of conductivity type of passive film from p-type to n-type, attributed to the chemical composition change.